Canadian Association of Radiologists Radiation Protection Working Group: Automated Patient-Specific Dose Registries—What Are They and What Are They Good for?. Issue 3 (August 2015) - Bjarnason, Thorarin A.; Thakur, Yogesh; Chakraborty, Santanu; Liu, Peter; O'Malley, Martin E.; Coulden, Richard; Noga, Michelle; Mason, Andrew; Mayo, John
Medical radiation should be used appropriately and with a dose as low as reasonably achievable. Dose monitoring technologies have been developed that automatically accumulate patient dose indicators, providing effective dose estimates and patient-specific dose histories. Deleterious radiation related events have prompted increased public interest in the safe use of medical radiation. Some view individualized patient dose histories as a tool to help manage the patient dose. However, it is imperative that dose monitoring technologies be evaluated on the outcomes of dose reduction and effective patient management. Patient dose management needs to be consistent with the widely accepted linear no-threshold model of stochastic radiation effects. This essay reviews the attributes and limitations of dose monitoring technologies to provoke discussion regarding resource allocation in the current fiscally constrained health care system.